Lower Extremity Avulsion Fractures in the Pediatric and Adolescent Athlete. Issue 4 (April 2017) - Schiller, Jonathan; DeFroda, Steven; Blood, Travis
Abstract : Lower extremity avulsion fractures are uncommon in the pediatric population and can be misdiagnosed without proper imaging and/or clinical suspicion for these injuries. The most common locations of avulsion injuries are the ischial tuberosity, anterior superior iliac spine, and anterior inferior iliac spine. Less often, avulsion fractures occur in the tibial tubercle, calcaneus, and greater and lesser trochanters. When treated properly with rest and altered weight bearing, most of these injuries heal without complication. Although surgical intervention is rarely necessary, it has a high degree of success when it is used. However, avulsion injuries are often misdiagnosed as muscle strains or apophysitis and are mistakenly treated with early range of motion. An error in diagnosis and/or management can cause nonunion or further displacement, which may require surgery. Improper identification of these injuries can also lead to nerve irritation, chronic pain, and gait dysfunction. Awareness of these injuries and their natural history is important because healed avulsion fractures may resemble neoplastic bone on radiographs.